Perancangan Sistem Kenaikan Gaji Berkala Berbasis Java Pada Sekretariat Daerah Kabupaten Aceh Tengah - Ira Zulfa; Richasanty Septima; Iwan Tona (Universitas Gajah Putih, 2022)
Purpose: To create a model of a periodic employee salary increase system that is useful for simplifying the fast, good, and efficient processing of employee rank and salary reports in this application, facilitating all types of administration (Wijaya, 2019). Research Methods: what is needed to apply for a periodic salary increase which is included in the KGB Submission menu which contains the requirements and files that must be completed for the progress of the salary increase, (Wardhani, Trinoto, & Kuncoro, 2021). Results: to find out the process and results of submitting periodic salary increases for employees at the Regional Secretariat of Central Aceh Regency (Setdakab) with the validation and results menu, users can easily monitor the submission of periodic salary increases that have been submitted, can quickly determine to what extent the process has been running so it works.